Assessment of Agricultural Innovation Transfer System in The Decentralization Era - Fawzia Sulaiman (Forum penelitian Agro Ekonomi, 2002)
EnglishThe slow process of technology transfer, which is suitable to the bio-physic and social economic of its intended users, has been realized as a serious impediment in the acceleration of agricultural development. In this decentralization era, the agricultural innovation transfer system becomes more complex that needs an adjustment to the changing strategic environment, which is specific to each respective regional area. The initiation of the Agency for Agricultural Research and Development in the establishment of the Assessment Institute for Agricultural Technology (AIAT) at the provincial level in 1994 intended to decentralize agricultural research and development. However after seven years of the AIAT establishment, the availability of specific agro-ecosystem technologies at the field level is still limited. The centralistic approach in the implementation of agricultural development in the last three decades and the weak linkage among institutions dealing with agricultural innovation transfer are considered to be the main impediments for an effective agricultural innovation transfer system. The implementation of decentralization policy in early 2001 has resulted in several fundamental changes in the organizational structure and management of government institutions dealing with agricultural innovation transfer. These changes have increased the ineffectiveness of extension organization and personnel. For this reason, deliberate efforts to strengthen the linkage among institutions that have extension function and the revitalization of extension organization and personnel, are badly needed, especially at the district level. The implementation of decentralization in agricultural development, including in agricultural innovation transfer, needs appropriate preparation and deliberate efforts from regional (provincial and district) administrators and central bureaucracies, whereas mutual support and reinforcement toward each other are the prerequisite to decentralization success. The purpose of this study was to identify the performance of agricultural innovation transfer system in the early implementation stage of the decentralization policy. IndonesianProses alih inovasi pertanian yang sesuai dengan kondisi bio-fisik, sosial ekonomi petani dan budaya setempat yang masih berjalan lambat telah lama di sadari sebagai hambatan dalam upaya akselerasi pembangunan pertanian. Pada era desentralisasi, sistem alih inovasi pertanian menjadi lebih komplek dan perlu pendekatan yang disesuaikan dengan lingkungan strategis yang ada dan sangat bervariasi antar provinsi dan kabupaten. Pembentukan Balai Pengkajian Teknologi Pertanian di tingkat regional/ provinsi pada tahun 1994 merupakan realisasi kebijaksanaan desentralisasi/regionalisasi dan penelitian pengembangan pertanian yang diinisiasi oleh Badan Penelitian dan Pengembangan Pertanian. Walaupun demikian, setelah lebih dari tujuh tahun didirikannya BPTP, ternyata ketersediaan teknologi tepat guna spesifik agroekosistem yang sesuai dengan kebutuhan petani masih terbatas. Lemahnya keterkaitan antarv berbagai lembaga yang mengemban fungsi alih inovasi pertanian, termasuk kelembagaan tani, serta pendekatan sentralistik di dalam pembangunan pertanian selama lebih dari tiga dekade dianggap sebagai faktor penghambat utama dari efektifitas sistem alih inovasi pertanian. Implementasi kebijaksanaan desentralisasi pada awal tahun 2001 telah mengakibatkan perubahan mendasar dari struktur organisasi dan manajemen institusi pemerintah yang mengemban fungsi penyuluhan pertanian. Perubahan dasar ini telah ,mengakibatkan kinerja dari sebagian besar organisasi dan personal penyuluh pertanian di tingkat provinsi dan kabupaten sangat menurun. Koordinasi yang efektif antar institusi yang mengemban fungsi penyuluhan, dan revitalisasi organisasi dan personal penyuluhan perlu memperoleh perhatian yang serius, terutama dari para penentu kebijaksanaan Pemerintah Daerah Tingkat II. Pada penerapan kebijaksanaan otonomi daera(OTDA) di dalam pembangunan pertanian, termasuk di dalam penyelenggaraan alih inovasi pertanian, diperlukan persiapan yang matang dan komitmen dari para penentu kebijaksanaan serta administrator di tingkat Daerah maupun Pusat. Penerapan kebijaksanaan desentralisasi, termasuk di dalam alih inovasi dan teknologi pertanian, akan berhasil bila ada upaya khusus untuk saling mendukung antar institusi terkait. Tujuan dari pengkajian ini adalah untuk mengidentifikasi kinerja dari sistem alih iovasi pertanian pada awal penerapan kebijaksanaan desentralisasi.